Feasible Size Ratio Prediction of Wind and PV Module for Energy Generation of Different Climatic Zones in India - Khandare, Ranjana; Chaudhary, Rubina (The Nucleus, 2024)
Solar and wind are renewable energy resources that are non-exhaustible, freely available, ecofriendly and capable for providing solutions to the power problems, which are recently being faced by India and all over the world. With increasing demand of generating electricity, wind and solar energies are not available all the time, the combined implementation of renewable resources such as wind and solar can meet the increasing demand of electricity. This Paper presents study about the Photovoltaic-Wind Hybrid System (PWHS) under six climate zones of India. The study is based on the size ratio of Average Solar Irradiation Energy (ASIE) and Average Wind Speed Energy (AWSE). Annually, the ASIE varied form 5.00 KWh/m2 to 6.50 KWh/m2 whereas the values of AWSE varied between 0.1 m/s and 2.4 m/s. After analyzing different climatic conditions, PWHS was designed. Through mathematically modeling and learning programming techniques, different size ratios were conformed. Linear programming was applied on average annual value of photovoltaic (PV) and wind, to determine the size ratio of PV wind among different climate zones.